TLR7 Controls VSV Replication in CD169+ SCS Macrophages and Associated Viral Neuroinvasion - Solmaz, Gülhas; Puttur, Franz; Francozo, Marcela; Lindenberg, Marc; Guderian, Melanie; Swallow, Maxine; Duhan, Vikas; Khairnar, Vishal; Kalinke, Ulrich; Ludewig, Burkhard; Clausen, Björn E.; Wagner, Hermann; et al. (Frontiers in Immunology, 2019)
Vesicular stomatitis virus (VSV) is an insect-transmitted rhabdovirus that is neurovirulent in mice. Upon peripheral VSV infection, CD169+ subcapsular sinus (SCS) macrophages capture VSV in the lymph, support viral replication and prevent CNS neuroinvasion. To date, the precise mechanisms controlling VSV infection in SCS macrophages remain incompletely understood. Here, we show that Toll-like receptor-7 (TLR7), the main sensing receptor for VSV, is central in controlling lymph-borne VSV infection. Complete loss of TLR7 function impedes VSV infection in the draining lymph nodes (dLN), attenuates viral replication in SCS macrophages and fuels CNS neuroinvasion. By generating novel TLR7 floxed mice, we interrogate the impact of cell-specific TLR7 function in anti-viral immunity after VSV skin infection. Our data suggests that TLR7 signaling in SCS macrophages supports VSV replication in these cells, increasing LN infection and may account for the delayed onset of VSV-induced neurovirulence observed in TLR7-/- mice. Overall, we identify TLR7 as a novel and essential host factor that critically controls anti-viral immunity to VSV. Furthermore, the novel mouse model generated in our study will be of valuable to shed light on cell-intrinsic TLR7 biology in future studies.